Ængstelige Hillbillies: Reaktionære artefakter og affekter i Trumps USA - Juncker, Clara; Kongerslev, Marianne (K&K - Kultur og Klasse, 2018)
This article explores memoirs that express the anger, anxiety, and spite which Donald J. Trump provoked and tapped into in speeches and other appearances during his run for president, feelings he continues to provoke through social media and public appearances. Taking our departure in texts created by members of the white American underclass, poor white Mountain Folk in the Ozarks and Appalachian regions, as well as displaced southern migrants in Ohio, the article investigates the anxious structure of ugly feelings (Ngai) and explores how these affects relate to the Culture of Honor in the US Mountain South. In memoirs the Southern mountain culture is portrayed as a self-segregating and proud culture that fosters independent, hardscrabble characters, who value a certain kind of honor. Therefore, the article explores the interaction between hate, anxiety, and desperation among hillbillies in the Rustbelt and mountain regions and the Culture of Honor they have been shaped by, a culture which activates traditional Southern values and norms about masculinity, whiteness, family, and reputation, while exposing an inner fragility that manifests as emotional projection, substance abuse, violence but also resilience.